Characteristics of injuries among young cross-country skiers. - Boguszewski Dariusz; Niemczyk Joanna; Adamczyk Jakub (Kharkov National Pedagogical University, 2011)
The aim of this study was to develop information about injuries in cadet and junior cross-country skiers. Material and methods. Fifty female (n=21) and male (n=29) competitors from Podhale were in research group. Skiers completed questionnaire. The questions concerned the location of injuries, types of injuries, methods of treatments and rehabilitation and recovery exercises. Results. The most frequent injury in the research group was bruises, cuts and sprains and muscle strain. Few people had suffered broken bones and muscle ruptures. The most of the skiers suffered knee injuries. As a treatment PRICEMM procedure has been introduced. The main method of recovery was rest from training. Conclusions. No correlation was found epidemiology of injuries and the treatment, gender, age, level of sport and the number of starts of the season. Sports training and recovery should be similar In each group (female and male competitors). Players starting considerably more likely to devote less time to treatment and improvement of injury.